Youth Participation in Peacebuilding in Somalia: Challenges and Opportunities - Ahmed, Abdiaziz Abukar (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on the analysis of the challenges and opportunities of youth participation in peacebuilding in Somalia. The main objectives of the study were: to analyse the challenges of youth participation in peacebuilding related to the power dimensions of levels and spaces in Banadir region, Somalia and to explore the opportunities of youth participation in peacebuilding related to the power dimensions of levels and spaces in Somalia. The researcher used a qualitative approach of research to collect and analyse secondary data. The secondary data was collected through documentary review of books, articles, journals, reports that involved visiting the libraries and internet for the analysis of important documents in the search for topic issues. The information gathered from secondary data was resourceful in preparing the study and giving the research a more defined perspective. The secondary data were edited to check the accuracy, consistency and completeness of the information. The main findings of the study were that that the challenges hindering youth participation in Somalia include: poverty, lack of access to quality basic services like education, lack opportunities for youth to participate in peacebuilding, rigid culture, corruption, weak governance, prevalence of violence and insecurity and lack of resources and funding. And the key opportunities available for youth to participate in peacebuilding entail: increase youth opportunities for employment with entrepreneurship, market-focused, and public-private efforts, increase youth access to and use of high-quality education, increase youth engagement in community and government, conduct nation-wide campaign awareness on youth participation in peacebuilding and open space for youth to be leaders in the public sphere to strengthen the rule of law. The study recommended that the Federal Government of Somalia should promote, promote positive change to steer youth participation in peacebuilding, put in place mechanisms that engage youth in a collaborative fashion at all stages, include conflict analysis modules in the curriculum at appropriate levels, make education inclusive of all minority groups, including those people with disabilities, maintain contact with the trained youth facilitators, ensure that education is both inclusive and relevant to local needs and dedicate funding streams for peacebuilding in order to promote youth participation in peacebuilding in Somalia